How to go digital free : expert tips to guide your digital detox - Fielding Banks, Orianna (Welbeck, 2020)
More and more we rely on digital connection to fulfil our needs. Skype and FaceTime have taken place of meetings; digital devices are used to entertain children instead of playing with them; non-urgent emails and texts are read and responded to whilst in the company of others, lessening personal connections. Through 100 simple tips, including self-help assessments, step-by-step programmes and rebalancing techniques, this essential guide shows you how technology can still play a useful and rewarding role in your life, but not at the expense of personal relationships and mental health.